Historical Movement of Humanistic Education: The Process of Personality Development - Khatri, Damber Bahadur (Curriculum Development Journal, 2024)
People can learn best if they work with their interest and initiation and find a conducive and respectful humane environment where their self-actualization towards the learning process takes place. The environment involves empathetic and inspiring behaviour of teachers, experiential learning, and interesting content. In the present Nepalese context, they are not in reach of students due to the influence of the teacher-centered model over educators, which has been a great concern in addressing the students’ personal growth. However, it could be achieved through humanistic education that promotes self-directed learning. This paper discusses the theoretical aspects of humanistic knowledge, including past studies and literature, and its practice in Nepalese school education. Based on the survey, also explores and suggests ways to treat the learners in a humanistic manner.